2019
DOI: 10.3389/fcimb.2019.00267
|View full text |Cite
|
Sign up to set email alerts
|

Host-Derived Delta-Like Canonical Notch Ligand 1 as a Novel Diagnostic Biomarker for Bacterial Sepsis—Results From a Combinational Secondary Analysis

Abstract: Background: Sepsis is a life-threatening syndrome, resulting from a dysbalanced host response to infection. However, especially the early, pro-inflammatory immune response in sepsis is similar to other inflammatory conditions without infectious cause, e.g., trauma or surgery. This aspect challenges the value of current biomarkers for diagnosis, as these are often broadly induced. We earlier identified Delta-like Protein 1 (DLL1), a canonical Notch ligand, to be released from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
5
24
0
Order By: Relevance
“…The soluble factor responsible for activating Notch signaling in recipient cells remains to be determined. Notch ligand DLL1 has been found in the plasma of sepsis patients and the soluble form of DLL1 was observed in cell supernatants of human monocytes (Hildebrand et al, 2019). It is therefore conceivable that soluble DLL1 may be one of the factors responsible for the effect observed in our study.…”
Section: Discussionmentioning
confidence: 56%
“…The soluble factor responsible for activating Notch signaling in recipient cells remains to be determined. Notch ligand DLL1 has been found in the plasma of sepsis patients and the soluble form of DLL1 was observed in cell supernatants of human monocytes (Hildebrand et al, 2019). It is therefore conceivable that soluble DLL1 may be one of the factors responsible for the effect observed in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, Hildebrand et al identified soluble Delta-like canonical Notch ligand 1 (DLL1) released from monocytes as a predictive marker for sepsis, with a performance superior to that of CRP and PCT 70 . It has also been suggested that Notch signaling is involved in regulating monocyte cell fate 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Delta-like canonical Notch ligand 1 (DLL1) has been used as a novel biomarker for sepsis during upregulation of the Notch pathway in human monocytes. 98 Quantification of soluble DLL1 in plasma has been performed using a commercially available ELISA kit. As the Notch Ligand 1 is implicated in TNBC, 99 this may also work in measuring downregulation of the Notch pathway during consumption of Notch pathway suppressers identified in Step 2.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, high plasma levels of genistein may indicate p53 is regulated by MDM2. Verheus et al 98 found that high plasma levels of genistein were associated with reduced breast cancer risk in Dutch women.…”
Section: Resultsmentioning
confidence: 99%